Elaboração, aplicação e avaliação psicológica de um protocolo para casos de disputa de guarda - Maiorki, Simone (2014)
Psychological testing in custody cases has recently increased due to the growing number of separations. Protocols that guide the evaluation in such cases are rare in Brazil. Due to this demand, this study intended to develop, implement and evaluate the efficiency of a psychological assessment protocol in custody dispute situations. Eleven families who filed a petition for an order of custody in the Family Court of a municipality in the metropolitan region of Curitiba / PR were evaluated. The study included parents, extended families (stepmother and stepfather), mental health and educational professionals and the children involved. The protocol was composed of 10 instruments: 7 of which were basic and 3 complementary. The basic protocol was constituted of: (1) Parental Relationship Evaluation System (SARP), which evaluated the parental relationship; This tool consists of three techniques: (a) semi-structured interviews, (b) a child evaluating protocol called My Paper Friend and (c) a scale graded by the evaluator; (2) Parenting Styles Inventory (IEP) to identify parental practices used by parents in the education of their children; (3) A scale to investigate Parental Alienation (EAP); (4) Stress Symptoms Inventory for Adults (ISSL); (5) Infantile Stress Scale (ESI); (6) Beck Depression Inventory (BDI); (7) The review of court proceedings through a record sheet. The Additional Protocol was composed of: (8) NICHD Protocol (National Institute of Child Heath and Human Development) of forensic interviews with children suspected of being abuse victims; (9) ASEBA, an inventory that assesses social, emotional and/or behavioral aspects of children and adolescents; (10) APSD, a scale indicative of serious antisocial behavior in childhood; The average time spent to perform the psychological assessment, from data collection to the delivery of reports was 38.0 hours. Twelve interviews were conducted in an average of one hour per family. Teachers were interviewed in four cases and psychologists in two cases. The protocol identified two parents with stress exhaustion, two with severe depression and six had severe parental alienation. There was one case of sexual abuse and a child with conduct disorder, who was referred to psychological and psychiatric treatment. Psychological treatment was advised for four parents. The evaluation indicated that the mother should have permanent custody in seven cases and father in three cases. In seven cases there was a sentencing hearing, in which the opinion of the judge followed the opinion of the expert.